Peran Komunikasi Pemerintah Dengan Mempromosikan Hasil Produksi UMKM Desa Pulau Tanjung Kabupaten Asahan - Sarah Oktaviani; Zulfahmi Zulfahmi (Universitas Muhammadiyah Sumatera Utara, 2023)
Micro, Small and Medium Enterprises (MSMEs) are fields that contribute to economic growth and can survive Indonesia's economic crisis. This is because MSMEs can absorb a very large workforce and are close to the common people. Tempe Lemet and Fan Cake SMEs are one of the creative houses located in Pulau Tanjung Village and the promotions carried out on Facebook social media have made SMEs increasingly well known by the public. The type of research used in this research is descriptive with qualitative methods with data collection techniques by conducting interviews and documentation. From the results of this study, the government's role in promoting MSME products has been going well. The role of the government is as a facilitator because the government plays a role in providing fan cake molds, as well as providing a platform for MSME players to promote their products through social media and marketplace applications. Facebook social media used in marketing UMKM products is not very effective in increasing sales, due to the lack of consumer demand through Facebook. The increase in sales that occurred was not only due to promotions carried out through Facebook content, but because the residents of Tanjung Island Village through direct communication with the quality of the product taste, and affordable prices.